2003
DOI: 10.1034/j.1600-0412.2003.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Periurethral connective tissue status of postmenopausal women with genital prolapse with and without stress incontinence

Abstract: Our results indicate an altered metabolism of connective tissue in the periurethral region with a significant decrease of collagen and vitronectin expression in postmenopausal women with pelvic floor relaxation with and without GSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
3
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 50 publications
2
35
3
3
Order By: Relevance
“…Periurethral connective tissue Fig. 5 Percentage of smooth muscle, striated muscle, and connective tissue of the urogenital diaphragmx undergoes alteration in postmenopausal women with genital prolapse with and without stress incontinence [12]. Cadaver studies show that, in older women, all layers of striated urethral muscle become thinner; 2% of striated muscle in the anterior urethral wall is lost per year between the age of 20 and 80 [13,14] and may be completely absent posteriorly [15].…”
Section: Discussionmentioning
confidence: 99%
“…Periurethral connective tissue Fig. 5 Percentage of smooth muscle, striated muscle, and connective tissue of the urogenital diaphragmx undergoes alteration in postmenopausal women with genital prolapse with and without stress incontinence [12]. Cadaver studies show that, in older women, all layers of striated urethral muscle become thinner; 2% of striated muscle in the anterior urethral wall is lost per year between the age of 20 and 80 [13,14] and may be completely absent posteriorly [15].…”
Section: Discussionmentioning
confidence: 99%
“…the supernatants corresponding to individual samples were then combined, and collagens were precipitated by addition of 4.0 M naCl to a final concentration of 2.0 M. Each precipitate was dissolved in 0.5 m acetic acid, and the solution was dialyzed against 0.02 m na 2 hpO 4 . precipitated collagens were redissolved in 0.5 m acetic acid, dialyzed exhaustively against 0.05 M acetic acid and finally lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…thus, there have been many studies throughout the literature in which collagen is analyzed in vaginal and uterine-supporting ligament biopsies procured at the time of a repair of prolapse in patients with prolapse or at the time of a hysterectomy in patients without prolapse. the comparison of these samples has provided conflicting results (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). trauma or pathology may lead to altered responses to mechanical stresses placed on connective tissue, producing changes in the Ecm.…”
Section: Introductionmentioning
confidence: 99%
“…From the study by Goepel et al who investigated several collagen types in the periurethral vagina wall in continent and incontinent postmenopausal women with POP, it seems that tissues from POP patients with GSI showed weaker immunostaining for types I, III, and IV collagens [17]. In agreement with these results, by investigating the same molecules and analyzing the immunostaining by automatic digital image analysis, Lin et al observed a significant reduction in only collagen III in the apex of the anterior vaginal wall in patients with POP [18].…”
Section: Collagenmentioning
confidence: 99%
“…Several studies have analyzed changes in the vaginal connective tissue of patients with and without POP by histology [12][13][14][15][16][17][18][19] using various methods and stainings to assess changes in collagen content in the vaginal wall. The results of these studies are described in Table 1.…”
Section: Collagenmentioning
confidence: 99%